Children Are Not Criminals: Exposing Errors in Drug Law Enforcement and Reconstructing a Restorative Justice-Based Approach - Andri Winjaya Laksana; Hendro Widodo; Dzaka Imtiyaz Iqbal; Dian Pramana; Vasyl Shevchenko (Nusantara: Journal of Law Studies, 2026)
Legal protection for children involved in narcotics cases remains a critical issue within Indonesia’s criminal justice system, particularly when children who use or abuse narcotics continue to be processed as offenders and subjected to imprisonment. This study aims to analyze weaknesses in the current enforcement of narcotics law concerning children and to formulate a restorative justice-based reconstruction that prioritizes child protection and rehabilitation. The research employs a socio-legal approach by examining statutory regulations, legal principles, and the implementation of law enforcement practices concerning children in conflict with the law. The findings reveal that law enforcement practices continue to emphasize punitive and retributive measures, despite the Juvenile Criminal Justice System Law requiring deprivation of liberty to be used only as a last resort and mandating that the best interests of the child be prioritized. In practice, children who use narcotics are frequently positioned as perpetrators rather than as vulnerable individuals requiring medical and social rehabilitation, contrary to Article 54 of the Narcotics Law. Several factors—including ambiguities in the legal framework, the dominance of repressive law enforcement paradigms, limited rehabilitation facilities, inadequate institutional coordination, and low public legal awareness of children’s rights—contribute to the ineffectiveness of legal protection. This condition hinders the implementation of restorative justice and undermines the fulfillment of children’s rights as a vulnerable group. Accordingly, this study proposes reconstructing Article 79 paragraph (1) and Article 82 letter (i) of the relevant legal framework by incorporating mandatory rehabilitation measures and replacing the terminology “users and abusers” with “addicts and victims of drug abuse.” This reconstruction contributes to strengthening a child-centered criminal justice system oriented toward recovery, protection, and social reintegration.